Nation of Islam dan Hak Sipil Kaum Kulit Hitam di Amerika Serikat (1930-1976) - Tia Oktarina (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
The Nation of Islam is a black organization that uses Islamic principles in its movement, the main goal of which is the freedom of black civil rights. The Nation of Islam has become a place of hatred for blacks against whites because of the racial discrimination they have experienced so far. Many researches on the civil rights of blacks in the United States have been written, but the struggle for civil rights by the Nation of Islam is still lacking, especially in Indonesia. The main discussion of the research is